Encyclopedia of Life Sciences 2013
DOI: 10.1002/9780470015902.a0020374
|View full text |Cite
|
Sign up to set email alerts
|

Biofuels: Fungal, Bacterial and Insect Degraders of Lignocellulose

Abstract: Lignocellulose is the main structural component of plant cell walls and can be degraded into simple sugars with the help of hydrolytic enzymes. Lignocellulose is composed of three polymers: cellulose, hemicellulose and lignin. Certain fungi, bacteria and insects have evolved the ability to degrade lignocellulose. Cellulose is degraded to glucose by the synergistic action of three distinct classes of enzymes: endoglucanases, exoglucanases and β‐glucosidases. Owing to its variable structure and organisation, hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 146 publications
2
11
0
2
Order By: Relevance
“…The presence of TFLs in translated GHF7 peptide sequences is a characteristic of some CBHs (also known as “exoglucanases”); whereas, a lack of TFLs is a characteristic of some EGases (e.g., Todaka et al., ; Zhou et al., , ; Sethi and Scharf, ). No TFLs were predicted in GHF7‐3, but two putative TFLs were present in GHF7‐5 and ‐6 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of TFLs in translated GHF7 peptide sequences is a characteristic of some CBHs (also known as “exoglucanases”); whereas, a lack of TFLs is a characteristic of some EGases (e.g., Todaka et al., ; Zhou et al., , ; Sethi and Scharf, ). No TFLs were predicted in GHF7‐3, but two putative TFLs were present in GHF7‐5 and ‐6 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lignocellulose is the most sustainable form of plant biomass available on Earth. Lignocellulose consists mainly of the β‐1,4‐sugar polymers cellulose and hemicellulose, and the phenolic polymer lignin (Pettersen, ; Sethi and Scharf, ). The major obstacle to efficient usage of lignocellulose as a feedstock in biofuel production is the inefficiency of industrial lignocellulose degradation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…cell wall has been described as a rigid wall of cellulose and hemicellulose, which together with the sporopollenin-like biopolymer provides great resistance to enzymatic degradation (Mendez et al, 2014;Mussgnug et al, 2010). Lu et al (2013) reported the occurrence of Lactobacillus and Clostridia in fresh pig manure, independent of pig age and diet, while other studies have shown that Lactobacillus and Clostridia are very effective at degrading cellulosic organic matter (Calderon Santoyo et al, 2003;Li and Liu, 2012;Mussatto et al, 2008;Sethi and Scharf, 2001).…”
Section: Of Supplementarymentioning
confidence: 99%